2022
DOI: 10.1093/ageing/afac149
|View full text |Cite
|
Sign up to set email alerts
|

Provision of a comprehensive medicines review is associated with lower mortality risk for residents of aged care facilities: a retrospective cohort study

Abstract: Background no studies have examined the impact of residential medication management review (RMMR, a 24-year government subsidised comprehensive medicines review program) in Australian residential aged care facilities (RACFs) on hospitalisation or mortality. Objective to examine associations between RMMR provision in the 6–12 months after RACF entry and the 12-month risk of hospitalisation and mortality among older Australians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Despite a high burden of medicines use in this population, and some evidence of benefits in reducing use of certain medicine classes and impact on health, we have found that Home Medicines Reviews and Residential Medication Management Reviews (RMMRs) (ie, comprehensive medicines reviews conducted by pharmacists in collaboration with general practitioner) are underutilised among aged care recipients 9. Specifically, we have reported modest changes in the use of six out of 14 medicine classes after an RMMR and a 4.4% lower mortality risk in those who received a RMMR 37. However, only one in five residents received a medication review within three months after entering an RACF and only 3.0% of home care package recipients received a review annually,36 despite recommendations for these services 31 38…”
Section: Findings To Datementioning
confidence: 98%
See 1 more Smart Citation
“…Despite a high burden of medicines use in this population, and some evidence of benefits in reducing use of certain medicine classes and impact on health, we have found that Home Medicines Reviews and Residential Medication Management Reviews (RMMRs) (ie, comprehensive medicines reviews conducted by pharmacists in collaboration with general practitioner) are underutilised among aged care recipients 9. Specifically, we have reported modest changes in the use of six out of 14 medicine classes after an RMMR and a 4.4% lower mortality risk in those who received a RMMR 37. However, only one in five residents received a medication review within three months after entering an RACF and only 3.0% of home care package recipients received a review annually,36 despite recommendations for these services 31 38…”
Section: Findings To Datementioning
confidence: 98%
“… 9 Specifically, we have reported modest changes in the use of six out of 14 medicine classes after an RMMR and a 4.4% lower mortality risk in those who received a RMMR. 37 However, only one in five residents received a medication review within three months after entering an RACF and only 3.0% of home care package recipients received a review annually, 36 despite recommendations for these services. 31 38 …”
Section: Findings To Datementioning
confidence: 99%
“…6,7 Health assessments, GP management plans and team care arrangements for older people receiving home care packages or medication reviews for people living in permanent residential aged care (PRAC) have been found to be associated with lower mortality rates. 8,9 Despite the Australian Medical Association's 2018 Position Statement calling for a national evaluation of the access and effectiveness of primary care services in the care of older people to ensure their needs are being met, no such evaluation has occurred to date. 10 In addition, given the recent Australian Government investments in aged care 11 and primary health care reforms, 12 an understanding of the access and trends in the use of primary, allied health and specialist services by Australian aged care recipients is necessary for future reform evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…A pharmacist-conducted medication review is a common intervention for reducing medicines-related harm in aged care residents (Ali et al, 2021). A previous study in Australia reported that the provision of pharmacist-led medication reviews appears to decrease the risk of mortality in residents (Sluggett et al, 2022). Evidence also indicates that the lack of accessibility to pharmacists is an important factor affecting the rational use of medicines in RACFs (Al-Jumaili and Doucette, 2017).…”
Section: Introductionmentioning
confidence: 99%